2011 International Conference on Parallel Processing 2011
DOI: 10.1109/icpp.2011.11
|View full text |Cite
|
Sign up to set email alerts
|

On the Performance of Greedy Algorithms for Power Consumption Minimization

Abstract: Abstract-We revisit the well-known greedy algorithm for scheduling independent jobs on parallel processors, with the objective of minimizing the power consumption. We assess the performance of the online version, as well as the performance of the offline version, which sorts the jobs by non-increasing size before execution. We derive new approximation factors, as well as examples that show that these factors cannot be improved, thereby completely characterizing the performance of the algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Bansal and Pruhs (2010) investigated several server scheduling problems, where the standard approach for balancing average QoS (Quality of Service) and fairness is to optimize the l p -norm. Benoit et al (2011) considered the objective of minimizing the total power consumed by the processors to execute the job, which is equivalent to the minimization of l 3 -norm.…”
Section: Literature Review Of Hierarchical Schedulingmentioning
confidence: 99%
“…Bansal and Pruhs (2010) investigated several server scheduling problems, where the standard approach for balancing average QoS (Quality of Service) and fairness is to optimize the l p -norm. Benoit et al (2011) considered the objective of minimizing the total power consumed by the processors to execute the job, which is equivalent to the minimization of l 3 -norm.…”
Section: Literature Review Of Hierarchical Schedulingmentioning
confidence: 99%
“…[1] showed that the problem of scheduling independent tasks can be approximated by a factor (1 + ε): they exhibit a polynomial time approximation scheme (PTAS). [9] studied the performance of greedy algorithms for the problem of scheduling independent tasks, with the objective of minimizing the energy consumption, and proposed some approximation algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…One may try to minimize the ℓ k norm, i.e., the quantity ( p q=1 ( i∈load(q) a i ) k ) 1/k , with p processors, where i ∈ load(q) means that task T i is assigned to processor q, and a i is the weight of task T i [1]. Minimizing the power consumption then amounts to minimize the ℓ 3 norm [9], and the problem of makespan minimization is equivalent to minimizing the ℓ ∞ norm, i.e., minimize max 1≤q≤p i∈load(q) a i [13,5]. These problems are typical load balancing problems, in which the load (computation requirement of the tasks) must be balanced between processors, according to various criteria.…”
Section: Introductionmentioning
confidence: 99%
“…e.g. [17]), which results in the relation between power cost and transmission speed given as P ∼ f 3 ( [4,5]). Such a model of power consumption was recently studied in the context of splittable Manhattan-path routing by Benoit et al [4].…”
Section: Introductionmentioning
confidence: 99%